Assessing the influence of actinic keratosis on patients' quality of life: the AKQoL questionnaire. (30th January 2013) - Esmann, S.; Vinding, G.R.; Christensen, K.B.; Jemec, G.B.E.
Summary Background Limited knowledge is available regarding quality of life in patients with actinic keratosis (AK). Objectives To develop and validate a disease‐specific questionnaire – the Actinic Keratosis Quality of Life questionnaire (AKQoL) – to assess the quality of life of patients with AK. Methods Based on an extensive literature search and patient interviews, the AKQoL was developed in a stepwise approach. An initial mega‐questionnaire was composed and subsequently shortened based on statistical differences between patients and controls. A test–retest was done to establish the reliability and to refine the items further. Rasch analyses were performed on the final questionnaire. Results Initially, 175 items were tested in a mega‐questionnaire. The questionnaires were sent out twice and statistical analyses were made, reducing the number of questions to 18 and 10, respectively. Subsequent inter‐item correlations showed that one item had only a weak correlation to the rest of the scale. This was confirmed by the Rasch model and by internal consistency as evaluated by Cronbach's coefficient alpha. Only one item was found to provide a small sex difference. A Bland–Altman plot showed excellent reliability. Items are scored on a standard 4‐point Likert scale and summarized in a total score of maximum 27 points. A higher score indicates greater quality of life impairment. Conclusions A nine‐item questionnaire for patients with AK was developed. The AKQoL has three domains covering emotions, function and control and one single global item. The questionnaire's scale structure, the content and face validity, and the reliability have been established.